Using graded readers for engaging CEFR A2 students to read for pleasure at Universidad Politecnica Salesian. - Vasco Muñoz, Jessica Isabel (2022)
This study reports on the use of graded readers as a vehicle to motivate students to read more in English. A month period was devoted for the implementation of this project. The participants of this study were twenty-seven students who belonged to the group 4202 which corresponds to an elementary level at Universidad Politecnica Salesiana in Guayaquil-Ecuador. The participants were asked to choose graded readers at the library of the university. Data obtained through speaking and writing diagnostic tests, a questionnaire about motivation and reading habits, quizzes, and interviews showed that using graded readers resulted in students’ improvement in vocabulary and writing skills. A mixed-methods approach was applied in order to integrate quantitative and qualitative data. The focus was based on action research for the betterment of reading practices. Likewise, this study examines how an appropriate selection of books can affect students’ perceptions about the work with graded readers